Cinema industry in Kazakhstan - Yelesh, Arman (My University, 2018)
Modern history of Kazakhstan cinema industry starts from 1991th after getting independence. Film producers created huge amount of movies for domestic market, during this period. Last 3 years this segment of entertainment became extremely attractive for cinemagoers and especially for production companies. In average companies produce from 40 to 60 films per year. Current situation had changed compared to last decade, when production of films was only 5 to 10 films per year. Therefore, this segment of economic is competitive due to presence of audience of 18 mln population and increasing interest of Kazakhstani films among citizens. This research is aimed to determine and asses current market situation in this sector of economic. In order to conduct research special questionnaire was created.
Keywords: cinema. cinema industry in Kazakhstan. cinemagoers. production of films